PENGEMBANGAN PEGAWAI NEGERI SIPIL - Ajib Rakhmawanto (Jurnal Manajemen Kepegawaian, 2009)
Development of civil servants is basically an effort to improve its quality and carrer. It is aimed to get its missionand goal to be real. For any civil servant, the development is perceived as a process to get and improve theirquality’carrer as well as their competence. It is necessary to formulate a development pattern on qualifiedcivil servant in order to achieve a synergy between civil servant and government mission. An implementationof civil servant development pattern might create professionals.Key words : civil servant, development, quality, and professional